Novel three-dimensional graphene nanomesh prepared by facile electro-etching for improved electroanalytical performance for small biomolecules. (March 2022) - Gong, Jiawei; Tang, Hongliang; Wang, Meifang; Lin, Xueting; Wang, Kailong; Liu, Jiyang
Graphical abstract: Highlights: 3D graphene nanomesh is prepared using electro-etching of 3D graphene. 3D graphene nanomesh has in-plane nanopores and abundant active sites. 3D graphene nanomesh exhibits high electrocatalytical ability. Selective determination of dopamine, uric acid and ascorbic acid in ternary mixture is achieved. Abstract: Facile, and low-cost preparation of three-dimensional graphene nanomesh (3D-GNM) with electrocatalytic sites and its application in electrochemical sensors is still a challenge. Herein, we demonstrate a fast and convenient strategy to prepare free-standing 3D-GNM, which possesses in-plane nanopores, artificial function edges and electrocatalytic properties. 3D graphene foam (3D-G) with monolithic and macroporous structure serves as the starting electrode. 3D-GNM is easily prepared by simple electrochemical polarization of 3D-G, including anodic oxidation (anodization, +5 V, in ionic liquid-IL electrolyte) and subsequent cathodic reduction (cathodization, −1 V, in phosphate buffer solution-PBS), which can be completed within 10 min. 3D-GNM exhibits well-separated oxidation peaks towards dopamine (DA), uric acid (UA), and ascorbic acid (AA). Compared with that on 3D-G, the oxidation potentials of DA, UA, and AA on 3D-GNM respectively have cathodic shifts of 180 mV, 130 mV and 290 mV and the current intensities of DA and UA increase by 52 times and 12 times. Selective determination of DA, UA and AA in ternary mixture (limit of detection is 0.26 μM, 6.0 nM and 3.1 μM, respectively) or biological (serum) samples is achieved.